Robin Hood. - Donald, Angus, 1965- (Narrativas históricas Edhasa., 2012)
In 1190 A.D. Richard the Lionheart, the new King of England, launches an epic crusade. His goal is to reclaim Jerusalem from the Saracens. Marching with the vast royal army is Britain's most famous, most feared, most ferocious warrior: the Outlaw of Nottingham, the Earl of Locksley--Robin Hood himself. With his band of loyal men at his side, Robin cuts a bloody swath on the brutal journey east. Daring and dangerous, he can outwit and outlast any foe, but the battlefields of the Holy Land are the ultimate proving ground, and within Robin's camp lurks a traitor--a hidden enemy determined to assassinate England's most dangerous rogue."